Rancang Bangun Perangkat Lunak Berbasis Web: Studi Kasus Pengiriman Barang - Eric Gunawan; Jonathan Jonathan; Jonathan Bosco Broto; Immanuela Puspasari Saputro (Universitas Islam Raden Rahmat, Malang, 2024)
This research develops a web-based freight forwarding system to improve the efficiency of shipping costs for customers. The system uses Agile methodology and real- time data to calculate the distance between the customer and the nearest warehouse and recommends the nearest warehouse when ordering. The system is designed to minimize shipping costs. Laravel framework is used to build the web application, and MySǪL as the database management system. The results show that the system provides warehouse location recommendations with a 97.4% success rate and has the potential to save shipping costs significantly. The system increases productivity at PT Sena Bhuana Mas by allowing customers to manually select warehouses and adjust to available stock. The system results in a more efficient and effective freight forwarding solution and increases productivity at PT Sena Bhuana Mas.